Designing Nonverbal Responses to Healthcare Robot Navigation Errors Through Performer-Based Enactments - Goo, Hideki Garcia; Evers, Vanessa (Anais da Conferência Latino-Americana de Interação Humano-Computador (CLIHC); 2026: Anais da XII Conferência Latino-Americana de Interação Humano-ComputadorDO - 10.5753/clihc.2026.21754, 2026)
Robots in public spaces will inevitably make mistakes, which can reduce user trust and acceptance. While verbal error mitigation strategies (e.g., apologies) are common, they may raise expectations of the robot’s social capabilities. This paper explores robot errors and nonverbal responses using movement, sound, and shape-change as expressive modalities in a hospital environment. We conducted a qualitative study with 26 performers who enacted social navigation error scenarios as either a healthcare robot or stakeholders. Through video analysis, results provide insights into how robots might recover from errors without relying on speech and demonstrate the value of performerinformed methods for designing expressive robot behaviors.